Relationship between skeletal muscle contractile properties and power production capacity in female Olympic rugby players - Valenzuela, P. L.; Montalvo, Z.; Sánchez-Martínez, G.; Torrontegi, E.; De La Calle-Herrero, J.; Dominguez-Castells, R.; Maffiuletti, N. A.; De La Villa, P. (European Journal of Sport Science, 2018)
This study aimed to determine which contractile properties measured by tensiomyography (TMG) could better differentiate athletes with high- and low-power values, as well as to analyse the relationship between contractile properties and power production capacity. The contractile properties of the vastus medialis (VM), rectus femoris (RF) and vastus lateralis (VL) of an Olympic women`s Rugby Sevens team (n = 14) were analysed before a Wingate test in which their peak power output (PPO) was determined. Athletes were then divided into a high-power (HP) and a low-power (LP) group. HP presented an almost certainly higher PPO (9.8 ± 0.3 vs. 8.9 ± 0.4 W kg-1, ES = 3.00) than LP, as well as a very likely lower radial displacement (3.39 ± 1.16 vs. 5.65 ± 1.50 mm, ES = 1.68) and velocity of deformation (0.08 ± 0.02 vs. 0.13 ± 0.03 mm ms-1, ES = 1.87) of the VL. A likely lower time of delay was observed in HP for all analysed muscles (ES > 0.60). PPO was very largely related to the radial displacement (r = -0.75, 90% CI = -0.90 to -0.44) and velocity of deformation (r = -0.70, 90% CI = -0.87 to -0.34) of the VL. A large correlation was found between PPO and the time of delay of the VL (r = -0.61, 90% CI = -0.84 to -0.22). No correlations were found for the contractile properties of RF or VM. These results highlight the importance of VL contractile properties (but not so much those of RF and VM) for maximal power production and suggest TMG as a practical technique for its evaluation.